Living with reservation : a "special" education for First Nations children - Pearson, Ingrid Pearson; University of Lethbridge. Faculty of Education (Lethbridge, Alta. : University of Lethbridge, Faculty of Education, 1995, 1995)
vii, 160 leaves 29 cm. This thesis represents an interpretive exploration into the experiences of First Nations' children who were receiving special education services and who had a history of receiving special education services. My purpose was to discover "What is a 'special' education for First Nations' children?" I began with the stories which brought me to this inquiry and the literature which connected with those stories. Then through open-ended interviews, eight First Nations' children gave stories that spoke of their experiences. My interpretations of their stories were reflected within the context of my non-Native culture, knowledge and experiences. The interpretations were offered as possible ways of seeing and knowing the experiences of the First Nations' children and as possible ways of opening oneself to respecting an-'other' way of seeing and knowing. My exploration led me to see anew what a 'special' education might be for First Nations' children.